118k views
18 votes
Solve: 6(1-3x) +2(2x-3)=0​

2 Answers

6 votes

Answer:

x = 0

Explanation:

→ Expand out the brackets

6 - 18x + 4x - 6 = 0

→ Collect all the like terms

-12x = 0

→ Now solve

x = 0

User Charlie Bear
by
4.5k points
6 votes

Answer:

0

Explanation:

6 ( 1 - 3x ) + 2 ( 2x - 3 ) = 0

First solve the brackets

6 - 18x + 4x - 6 = 0

Now combine like terms

6 - 14x - 6 = 0

And now let us solve for x

-14x = 6 - 6

Divide both sides by (- 14)

-14x = 0

x = 0

Hope this helps you :-)

Let me know if you have any other questions :-)

User JayminLimbachiya
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.